Suzuki–Miyaura Cross-Coupling Reactions in Acetic Acid Employing Sydnone-Derived Catalyst Systems - Lücke, Ana-Luiza; Wiechmann, Sascha; Freese, Tyll; Schmidt, Andreas (Synlett, 2017)
The catalyst system consisting of lithium N-phenylsydnone-4-carboxylate/Pd(PPh3)4 has proven to be an effective catalyst for the Suzuki–Miyaura reaction of 2,4-dinitrochlorobenzene with boronic acids in acetic acid at pH 5.7, whereas the N-phenylsydnone carbene palladium complex [sydPd(PPh3)2Br] required pH 8.0.
Keywords: catalysis; Suzuki–Miyaura reaction; N-heterocyclic carbenes; sydnones; palladium; pH value